Tonometria e ecobiometria ocular em tucano-toco (Ramphastos toco) e tucano-de-bico-verde (Ramphastos dicolorus) - Marchan, Pedro Rafael Apulcro Correa (2015)
The eyesight of birds is essential for their survival in a free environment; tiny alteration in this organ may cause loss of vision, consequently the difficulty or even the impossibility to hunt, move or protect themselves from predators; due to these particularities, the objective of this paper was to know the normal rate of intra-ocular pressure (IOP) and to identify the ocular anatomy through sonographic biometry in B-scan through transpalpebral way, so the ophthalmic examination can be complete and reliable. It was valued the IOP of 15 Toco Toucans (Ramphatos toco) and 15 Red-breasted Toucan (Ramphastos dicolorus) through applanation tonometry, using a Tono-Pen VET® tonometer and executed sonographic biometry ocular in 5 Toucans Toco and in 5 Red-breasted Toucan. The IOP from Toco Toucans, reliable in 95% got the media between 13,79 mmHg to17,61 mmHg, while the Red-breasted Toucan got the IOP between 12,05 mmHg and 16,81 mmHg. The ocular ultrasound eye was efficient as it could identify the previous segment, the lens, the posterior segment, positioning of the retina, Pecten and retrobulbar space. The Toco Toucans sonographic biometry obtained the bulbar average axial length of 1,66 cm, axial shaft of anterior segment 0,25 cm, shaft axial lens 0,35 cm axial shaft of posterior segment 1,05 cm, transverse shaft of the posterior segment 2,20 cm, transverse shaft of the lens 1,21 cm, and in Red-breasted Toucan the bulbar average axial length of 1,29 cm, axial shaft of anterior segment 0,10 cm, axial shaft lens 0,40 cm axial shaft of posterior segment 0,79 cm, shaft transverse of the posterior segment 1,39 cm, shaft transverse of the lens 0,99 cm. It follows that it is possible to measure IOP by tonometry with Tono-pen VET® tonometer and ocular sonographic biometry the B-scan transpalpebral, route is feasible for these species.